Machine Learning-Predicted Progression to Permanent Atrial Fibrillation After Catheter Ablation - Park, Je-Wook; Kwon, Oh-Seok; Shim, Jaemin; Hwang, Inseok; Kim, Yun Gi; Yu, Hee Tae; Kim, Tae-Hoon; Uhm, Jae-Sun; Kim, Jong-Youn; Choi, Jong Il; Joung, Boyoung; Lee, Moon-Hyoung; et al. (Frontiers in Cardiovascular Medicine, 2022)
Introduction: We developed a prediction model for atrial fibrillation (AF) progression and tested whether machine learning (ML) could reproduce the prediction power in an independent cohort using pre-procedural non-invasive variables alone. Methods: Cohort 1 included 1,214 patients and cohort 2, 658, and all underwent AF catheter ablation (AFCA). AF progression to permanent AF was defined as sustained AF despite repeat AFCA or cardioversion under antiarrhythmic drugs. We developed a risk stratification model for AF progression (STAAR score) and stratified cohort 1 into three groups. We also developed an ML-prediction model to classify three STAAR risk groups without invasive parameters and validated the risk score in cohort 2. Results: The STAAR score consisted of a stroke (2 points, p=0.003), persistent AF (1 point, p=0.049), left atrial (LA) dimension ≥43 mm (1 point, p=0.010), LA voltage <1.109 mV (2 points, p=0.004), and PR interval ≥196 ms (1 point, p=0.001), based on multivariate Cox analyses, and it had a good discriminative power for progression to permanent AF (area under curve [AUC] 0.796, 95% confidence interval [CI]: 0.753-0.838). The ML prediction model calculated the risk for AF progression without invasive variables and achieved excellent risk stratification: AUC 0.935 for low-risk groups (score=0), AUC 0.855 for intermediate-risk groups (score 1 3), and AUC 0.965 for high-risk groups (score  4) in cohort 1. The ML model successfully predicted the high-risk group for AF progression in cohort 2 (log-rank p<0.001). Conclusions: The ML-prediction model successfully classified the high-risk patients who will progress to permanent AF after AFCA without invasive variables but has a limited discrimination power for the intermediate-risk group.